International Agreements of the European Union: Division of Competences between a Supranational Organization and its Member States - Schlemmer, Michael André (Revista Tribuna Internacional, 2019)
Globalization and its subsequent changes in global trade have led to an increase in importance of International Agreements and to the necessity of European Union Member States to appear united. In this context, the possibility of the conclusion of International Agreements by the EU as a supranational organization instead of each individual Member State is the subject of this paper. The EU’s competence, the general conclusion process, legal effects as well as the Common Commercial Policy as a topic of highest relevance in connection with International Agreements are elaborated in detail. This is achieved through a comprehensive research and evaluation of international literature along with case law and opinions of the European Court of Justice. Moreover, the discussion of controversial questions aims to clarify practice-related issues.